Strategi dan Pertimbangan Etis dalam Penulisan Proposal Penelitian Ilmu Perpustakaan dan Informasi - Mufid, Mufid (TIK ILMEU : Jurnal Ilmu Perpustakaan dan Informasi, 2017)
In the preparation of an effective research proposal in library and information science, a researcher needs to have a proposal writing strategy, and to understand of the ethical issues of research either through qualitative, quantitative or mixed methods. Therefore, this paper aims to provide a guidance for a researcher about writing strategies that includes nine key elements of the arguments, the research proposal outlines, the effectively research proposal writing stages, and the ethical issues during the research. The ability of a researcher to choose a strategy, and to understand the ethical issues of research is very important. Its will determine the quality of research outputs